PENGARUH PENDIDIKAN DAN KOMPENSASI TERHADAP KINERJA DIVISI NEW PRODUCT DEVELOPMENT (NPD) PADA PT. MAYORA INDAH Tbk. - Agustin, Putri; Permatasari, Rita Intan (JURNAL ILMIAH M-PROGRESS, 2020)
This research aims to determine the Effect of Education and Compensation on the Performance of theNew Product Development (NPD) Division at PT. Mayora Indah Tbk partially and simultaneously. Thepopulation of this research is the employees of the New Product Development Division (NPD) with thesampling technique using saturated samples as many as 40 respondents. Quantitative associativequantitative data analysis techniques using multiple linear regression tests, partial and simultaneoushypothesis tests were processed using the SPSS program version 21.0The results of this study indicate that education has no partial effect on performance, compensation hasa partial effect on performance but education and compensation have a simultaneous effect on performance.The coefficient of determination (R2) obtained to determine the contribution of education and compensationvariables to performance was 11.1%, the rest 88.9% was influenced by other variables.Keywords: education, compensation, performance, mayora indah tbk.